Atrial fibrillation trial to evaluate real-world procedures for their utility in helping to lower stroke events: A randomized clinical trial. Issue 3 (April 2021) - Huang, Wen-Yi; Lee, Meng; Sung, Sheng-Feng; Tang, Sung-Chun; Chang, Kuo-Hsuan; Huang, Yung-Sung; Lee, Jiann-Der; Lee, Tsong-Hai; Jeng, Jiann-Shing; Chung, Chang-Min; Wu, Yi-Ling; Hsieh, Tsung-Ta; et al.
Background: Enhancing detection of unrecognized atrial fibrillation among acute ischemic stroke patients is crucial for secondary stroke prevention. Aim: To evaluate whether the detection rate of new atrial fibrillation in acute ischemic stroke patients without known atrial fibrillation could be improved by doing serial 12-lead electrocardiograms once daily for five days, compared with conventional 24-h Holter monitoring (24-h Holter). Methods: We conducted a randomized clinical trial to compare the detection rates of paroxysmal atrial fibrillation between serial electrocardiograms versus 24-h Holter from October 2015 to October 2018 at six hospitals. Eligible participants were acute ischemic stroke patients with aged ≥65 years, with neither atrial fibrillation history nor any presence of atrial fibrillation on baseline electrocardiogram at admission. The primary outcome was newly detected electrocardiogram in the serial electrocardiograms and 24-h Holter group. Results: Among 826 patients, baseline characteristics were similar between both groups. In the intention-to-treat analysis, there was no statistical difference between serial electrocardiograms versus 24-Holter to detect atrial fibrillation (8.4% vs. 6.9%; adjusted odds ratio 1.17, 95% confidence interval 0.69–2.01). Stepwise multivariate logistic regression revealed age ≥80 years and history of heart failure were associated with detection of paroxysmal atrial fibrillation whereas patients with lacunar infarction had lower odds for detection of paroxysmal atrial fibrillation. Conclusions: Serial electrocardiograms had comparable detection rate of paroxysmal atrial fibrillation compared with 24-h Holter and might be a viable alternative to 24-h Holter as a first-line approach to survey for potential paroxysmal atrial fibrillation among elderly patients with acute ischemic stroke. Clinical Trial Registration: URLhttps://clinicaltrials.gov/ct2/show/NCT02578979 Unique Identifiers: NCT02578979